Pelestarian Kuliner Tradisional Gulai Ayam Lado Kotiang Jorong Lompek sebagai Warisan Cita Rasa Nagari Halaban melalui Program KKN UNP - Anisa Wulandari; Ratna Wilis; Cintya Ekwirosa; Sefty Novitasari; Muhammad Alvin Nurdin; Sukma Julita; Alaa Rifkiyah Zahra; M. Arfan Dzaki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Community Service Program (KKN) of Universitas Negeri Padang (UNP), conducted in June– July 2025 in Jorong Lompek, Nagari Halaban, Lareh Sago Halaban District, Lima Puluh Kota Regency, represents a form of student service to the community in developing local potential. One of the main focuses of this KKN activity is the preservation of traditional cuisine, particularly gulai ayam lado katiang, as a cultural heritage and a signature flavor of the Minangkabau people. This dish is uniquely rich in flavor, cooked with ruku-ruku leaves as a natural aromatic and karambia randang (black roasted coconut) as a source of savory taste and deep color. Through observation, interviews, documentation, and outreach to the local community and younger generations, UNP students sought to revive local culinary values that are becoming increasingly unfamiliar. This activity aims not only to preserve regional culinary identity but also to support the cultural and gastronomic tourism potential of Nagari Halaban. Hence, preserving gulai ayam lado katiang not only strengthens community bonds but also becomes a part of a broader strategy for local-based development.